ENHANCEMENT OF ORAL BIOAVAILABILITY TELMISARTAN FAST-DISSOLVING TABLETS EMPLOYING SWEETSOP STARCH AS A NEW SUPERDISINTEGRANT - RAMA CHAKRADHAR DEVANI; SANTOSH KUMAR RADA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Telmisartan is a BCS class-II drug with low bioavailability (42-58%) due to its poor solubility. To enhance the solubility and bioavailability, it can be formulated in Fast Dissolving Tablets (FDTs) employing Sweetsop starch as a new natural superdisintegrant through a 23 factorial design. Methods: Sweet Sop Starch (SSS) was extracted from the pulp of Annona squamosa L. The micromeritics characteristics of SSS were assessed, and the resulting product was utilized as a new superdisintegrant in the direct compression method of formulating Telmisartan (TSN) FDTs. The SSS was evaluated employing Fourier-transform infrared spectroscopy (FTIR), powdered x-ray diffraction, differential scanning calorimetry, and scanning electron microscopy. SSS, Potato starch (PS), and Sodium Starch Glycolate (SSG) were employed as superdisintegrants, and factorial design was used to investigate their disintegration property, Wetting Time (WT), and in vitro dissolution. The hardness, friability, homogeneity of Drug Content (DC), Water Absorption Ratio (R), in vivo pharmacokinetics, and stability parameters of formulated TSN FDTs were assessed. Results: Micromeritic characteristics revealed that the produced SSS was fine, free-flowing, and crystalline. FTIR and DSC investigations indicated that there were no drug-excipient interactions. From the prepared formulations (F1 to F8), the one with a 5% SSS containing formulation TF2, demonstrated 98.44±1% drug release within ten minutes with 59±0.14secWTand had 42±01 sec DT. The optimized formula attained peak plasma concentration extremely quickly and showed 76.05 % relative bioavailability. Conclusion: The formula containing 5% SSS showed good mechanical and physical characteristics, increased drug dissolution, and promoted quick disintegration with enhanced relative bioavailability in the management of hypertension and patient acceptance.